Consecutive days of high intensity training and its effect on markers of oxidative stress in highly trained cyclists - Shing, C.; Ahern, S.; Coombes, J.; Jenkins, D. (Australian Conference of Science and Medicine in Sport and Third National Sports Injury Prevention Conference: 2003. Tackling the barriers of performance and participation, 2003)
The purpose of the present study was to investigate the effects of three consecutive days of high-intensity training on markers of oxidative stress in eight highly-trained (VO2peak = 76 ± 4 ml.kg-1.min-1) male road cyclists. Over three consecutive days, subjects completed: 1) an interval session (IS; 9 x 30s at 150% of peak power output), 2) a 30-km cycle time trial (TT30), and 3) a second TT30. Four to six days later, subjects performed a submaximal trial (SM) at an oxygen consumption equivalent to that consumed during the IS. Fasted blood and urine samples were collected pre- and post-exercise for each trial. Erythrocytes were analysed for glutathione peroxidase (GPX) and catalse (CAT) activities. Plasma total antioxidant status (TAS), and urinary allantoin concentrations were also determined. GPX and CAT were found to be unchanged following the exercise trials and over time, however, TAS was significantly increased following the IS and the first TT30 (P < 0.01). Pre-exercise TAS values were also significantly higher for the first TT30 compared to the IS (P < 0.05). Urinary allantoin concentrations were significantly increased from pre-exercise values following the IS (2.98 ± 1.97 ìmol/min vs 6.86 ± 2.52ìmol/min; mean ± SD). The magnitude of allantoin concentrations pre- and post-exercise for the three consecutive days was significantly different (P <0.001). The present data suggest that consecutive days of high-intensity training amongst highly-trained road cyclists enhance resting plasma TAS, and reduce the magnitude of change in allantoin and TAS, which may represent an adaptation to the exercise stress.